Proposal for a South African spatial data infrastructure (SASDI) stakeholder collaboration framework, informed by the case of geospatial data for the municipal land use application process - Coetzee, Serena Martha (University of Pretoria, 2023)
Thesis (PhD (Geoinformatics))--University of Pretoria, 2023.